Pearl Catfish Pond Water Quality Monitoring System Using the ThingSpeak Server - Saskia, Kevi Agis; Suroso, Suroso; Salamah, Irma (Universitas Negeri Padang, 2024)
The research is centered around the implementation of an IoT-based water quality monitoring system for Pearl catfish ponds. This system uses ThingSpeak server to monitor pH, turbidity, temperature, and ammonia levels to maintain ideal conditions for fish growth. Data is processed using fuzzy logic. The results are sent in real time to the ThingSpeak server for continuous monitoring. The overarching goal of this system is to optimize production efficiency and improve the quality of fish for catfish farmers. The research has successfully developed an Internet of Things (IoT)-based water quality monitoring system for catfish ponds, demonstrating the positive impact of probiotics on both water quality and fish growth. Notably, Fishpond A, which received probiotic treatment, demonstrated notably superior water quality in comparison to Pond B without probiotics. Additionally, fuzzy logic testing indicated a high degree of accuracy, underscoring the system's effectiveness in real-time water condition monitoring.